Dialogue in the Poetry of Muslim ibn al-Walid (College of Basic Education Research Journal, 2025)
Dialogue is an  element of narrative style ,  poets  employed it in their poems since  pre-Islamic era , through  early Islamic period , to reach Umayyad era , Its use increased among Abbasid poets , to mention but one, Muslim ibn al-Walid , This  research explores  effectiveness of dialogue in his poetry and how he employs it as a means to express  ideas and feelings deeply embedded within his poet . Study aims to uncover  methods and techniques used by  poet to employ dialogue .
Keywords: Learning together strategy; social interaction; special education students